2018
DOI: 10.3390/ijms19103147
|View full text |Cite
|
Sign up to set email alerts
|

Histone Hyperacetylation as a Response to Global Brain Ischemia Associated with Hyperhomocysteinemia in Rats

Abstract: Epigenetic regulations play an important role in both normal and pathological conditions of an organism, and are influenced by various exogenous and endogenous factors. Hyperhomocysteinemia (hHcy), as a risk factor for several pathological conditions affecting the central nervous system, is supposed to alter the epigenetic signature of the given tissue, which therefore worsens the subsequent damage. To investigate the effect of hHcy in combination with ischemia-reperfusion injury (IRI) and histone acetylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…(a,b) Bar = 500 µm; (c,d) Bar = 50 µm; n = 5/group. Schematic coronal rat brain section (e), redrawn according to Tothova et al [12] representing hippocampus (blue rectangle) and smaller (red rectangle) detects CA1 area of rat hippocampus.…”
Section: Volumetric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(a,b) Bar = 500 µm; (c,d) Bar = 50 µm; n = 5/group. Schematic coronal rat brain section (e), redrawn according to Tothova et al [12] representing hippocampus (blue rectangle) and smaller (red rectangle) detects CA1 area of rat hippocampus.…”
Section: Volumetric Analysismentioning
confidence: 99%
“…This hHcy condition resulted in the disintegration of neuronal tissue in the cerebral cortex as well as the hippocampus. Moreover, Tóthová et al [12] have shown that hHcy on the same rat model also triggers remarkable epigenetic changes with the impairment in histone acetylation, likely within the context of hHcy-initiated DNA hypomethylation in vulnerable brain areas [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work on the rat hHcy model induced by a Met-enriched diet [ 20 ], we have revealed considerable cerebral dysregulations: (i) on the level of cerebral metabolites, and (ii) histologically detected acceleration of the hippocampal neurodegeneration. Previous papers from our laboratory [ 21 , 22 , 23 , 24 ] documented that the combination of hHcy induced by direct Hcy injection with the subsequent ischemia-reperfusion insult (IRI), aggravates neurodegenerative processes and might eventually lead to the development of AD-like pathology [ 22 , 23 ]. Using a novel methodological approach, we demonstrate here that the rats with the Met-enriched diet (inducing hHcy) were subject to the IRI manifested exacerbated patterns of hippocampal neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, overexpressed eNOS in transgenic mice renders them resistant to stress-induced hypotension, inflammation, and stroke ( Beck & Plate, 2009 ). It is well established that global ischemia, caused by reduced cerebral blood flow, initiates a cascade of mechanisms, including elevated levels of ROS, excitotoxicity, mitochondrial dysfunction and neuronal apoptosis ( Tóthová, Kovalská, Kalenská, Tomašcová, & Lehotský 2018 ). Accordingly, eNOS has a neuroprotective role by increasing blood flow in the very early stages of cerebral ischemia ( Hashiguchi et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%